Authenticity in Influencer Marketing: How Can Influencers and Brands Work Together to Build and Maintain Influencer Authenticity? - Duffek, Barbara; Eisingerich, Andreas B.; Merlo, Omar; Lee, Guan (Journal of Marketing, 2025)
This study examines how different stakeholders perceive influencer authenticity, revealing the misalignments that arise when each group prioritizes different aspects of authenticity. In doing so, the authors generate new theory on influencer marketing and provide managerial insights for brands and agencies to collaborate effectively with influencers to resolve these misalignments and ultimately build and sustain influencer authenticity. Using exploratory, in-depth interviews with consumers, influencers, brand managers, and influencer marketing agencies, the study triangulates stakeholder perspectives on influencer authenticity. Specifically, it examines the misalignment among these groups through the lens of assemblage theory and explores how these misalignments may be resolved to produce successful and lasting influencer assemblages. Finally, it explores how influencer marketing agencies can help manage authenticity misalignments.